(−)-Epicatechin exerts positive effects on anxiety in high fat diet-induced obese mice through multi-genomic modifications in the hippocampus. Issue 20 (28th September 2022) - Kang, Jiye; Oteiza, Patricia I.; Milenkovic, Dragan
Abstract : (−)-Epicatechin exerts complex genomic modifications in the hippocampus, counteracting changes driven by consumption of the high fat diet and/or associated obesity. Abstract : Obesity is associated with increased occurrence of cognitive and mood disorders. While consumption of high-fat diets (HFD) and associated obesity could have a detrimental impact on the brain, dietary bioactives may mitigate these harmful effects. We previously observed that (−)-epicatechin (EC) can mitigate HFD-induced anxiety-associated behaviors in mice. The aim of our study is to investigate the molecular mechanisms of EC actions in the hippocampus which underlies its anti-anxiety effects in HFD-fed mice using a multi-genomic approach. Healthy eight-week old male C57BL/6J mice were fed for 24 weeks either: (A) a control diet containing 10% total calories from fat; (B) a HFD containing 45% total calories from fat; or (C) the HFD supplemented with 20 mg EC per kg body weight. Hippocampi were isolated for genomic analysis using Affymetrix arrays, followed by in-depth bioinformatic analyses. Genomic analysis demonstrated that EC induced significant changes in mouse hippocampal global gene expression. We observed changes in the expression of 1001 protein-coding genes, 241 miRNAs, and 167 long non-coding RNAs. Opposite gene expression profiles were observed when the gene expression profile obtained upon EC supplementation was compared to the profile obtained after consumption of the HFD. Functionality analysis revealed that the differentially expressed genes regulate processes involved in neurofunction, inflammation, endothelial function, cell–cell adhesion, and cell signaling. In summary, the capacity of EC to mitigate anxiety-related behaviors in HFD-induced obese mice can be in part explained by its capacity to exert complex genomic modifications in the hippocampus, counteracting changes driven by consumption of the HFD and/or associated obesity.